Implikasi Kompetensi Kepribadian Guru PAI Terhadap Peningkatan Kesalehan Sosial Peserta Didik - Abdillah, Syaik; Munawar, Ikbal (STAI Al-Musaddadiyah Garut, 2023)
This research is motivated by observations indicating an increase in the social piety of students within a particular school. This enhancement is attributed to the role of teachers, which cannot be separated from their competencies, particularly their personality competence. To educate and shape students with noble character (akhlakul karimah) and to achieve this increase in piety, teachers must possess strong personality competence. The objectives of this study are: 1) To describe the Social Piety of Students at SMP Plus Miftahul Hidayah, 2) To describe the Personality Competence of Islamic Religious Education (PAI) Teachers at SMP Plus Miftahul Hidayah, and 3) To describe the Implications of PAI Teachers' Personality Competence on the Enhancement of Students' Social Piety at SMP Plus Miftahul Hidayah. The research employs a qualitative descriptive method, complemented by a literature review approach. The data sources include primary data obtained from interviews with PAI teachers at SMP Plus Miftahul Hidayah, and secondary data from books or other reading materials directly related to this study. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that the personality competence of teachers significantly impacts the increase in students' social piety. This is because teachers with strong personality competence contribute to enhancing the social piety of their students. Keywords: Personality Competence of PAI Teachers, Social Piety